Specjalne strefy ekonomiczne i ich funkcjonowanie w obrębie dużych miast Polski - Hajduga, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The above article describes special economic zones and their function within Polish big cities. Special economic zones (SEZ) are an instrument of a State affecting the national economy. The Polish special zones are generally distracted and SEZs are functioning in different cities. The main aim of this paper is to present an important role of special economic zones in the development of Polish cities and regions. In the first part, different definitions and functions of SEZs were discussed. In the second part the author described the Wałbrzych Special Economic Zone "INVEST-PARK" and Legnica Special Economic Zone and also showed the benefits of their activity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 148-159